Effects of human capital, natural resource, urbanization, energy consumption on carbon emissions in the top ten emitter countries. Issue 3 (25th December 2023) - Zhang, Yu-Chen; Liu, Xi-Hua; Ullah, Arif; Mehmood, Usman
Abstract: The entire world is facing the problem of changing climate and distortion of environmental quality due to the rapid increase in carbon emissions. Therefore, this study was planned to examine the world's top ten carbon emitter countries, and the time extent was from 1990 to 2019. We employed panel Kao cointegration and Pooled Mean Group (PMG) techniques to explore the effect of human development, natural resources, urbanization, and energy use on carbon emissions. The Kao cointegration test results reveal that endogenous variables in the study have robust cointegration with carbon emissions. The PMG techniques results suggest that natural resources, urbanization, and energy use positively impact carbon emission in the top ten carbon emitters countries. Conversely, human development has a negative impact on carbon emission in the selected sampled nations. Based on the study's outcomes, the officials and policymakers of the sampled selected countries must set a policy to ensure environmental sustainability despite slowing down the process of economic development. More efforts are required to improve the human development index in the sampled selected economies. The overexploitation of natural resources should be revoked immediately to avoid more environmental damage. Further, green energy and urbanization should be introduced and publicized more effectively among society.